Typhoon and flooding occurrences on Chongming Island, Changjiang Estuary, as revealed by a newly acquired sedimentary record - Zhao, Peipei; Yang, Yang; Jia, Jianjun; Zhao, Ning; Zhang, Wentong; Gao, Shu (Frontiers in Marine Science, 2024)
Typhoon-induced storms surges and river flooding events represent two types of natural disasters that affect a wide range, occurring with high frequency and causing serious societal losses. Due to the limited duration of instrumental records, there is an inadequate understanding of the patterns and mechanisms underlying the variations in typhoons and floods. The interpretation of sedimentary records aptly compensates for these deficiencies in terms of the temporal scale, becoming a crucial medium for extending the temporal span of typhoon and flood records. Previous studies in this field have primarily focused on the identification of single types of extreme events. The Changjiang Estuary, particularly Chongming Island, is significantly affected by both typhoons and river floods, making it an excellent area for synchronous comparative studies of these two types of extreme events. Based on the analysis of a core sample, ZP02, collected from Chongming Island, in terms of chronological, sedimentological, and geochemical characteristics, specific tracing fingerprints for event deposits from typhoon and flood events are established. Sediments from typhoon events generally exhibit erosive contact surfaces, coarser grain sizes, and a tendency to become finer upwards, often featuring layers mixed with coarse sand and shell fragments. In contrast, flood event deposits vary in grain size, either coarser or finer, with abrupt contact surfaces compared to normal sediment layers, and are predominantly brownish-yellow in color. The fingerprint tracing results indicate that the typhoon event layers are characterized by high values in principal component 2 (PC2) of the elements, Zr/Fe and Sr/Fe ratios, with low values in principal component 1 (PC1) the elements and Ti/Ca ratio. Flood event deposits are marked by high values in PC1 and Ti/Ca ratio, low values in PC2 and Sr/Fe ratio, and an increase in Zr/Fe ratio in coarser flood layers but no significant change in finer layers. Based on these fingerprints, 19 layers of typhoon and the same number of flood events were identified in core ZP02, which correspond well with documentary records. The establishment of tracing fingerprints for typhoon and flood event deposits provides methodological support for the identification and interpretation of various extreme event deposits.